2016
DOI: 10.1038/leu.2016.126
|View full text |Cite|
|
Sign up to set email alerts
|

RUNX1 mutations in acute myeloid leukemia are associated with distinct clinico-pathologic and genetic features

Abstract: We evaluated the frequency, genetic architecture, clinico-pathologic features and prognostic impact of RUNX1 mutations in 2439 adult patients with newly-diagnosed acute myeloid leukemia (AML). RUNX1 mutations were found in 245 of 2439 (10%) patients; were almost mutually exclusive of AML with recurrent genetic abnormalities; and they co-occurred with a complex pattern of gene mutations, frequently involving mutations in epigenetic modifiers (ASXL1, IDH2, KMT2A, EZH2), components of the spliceosome complex (SRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
185
9
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(232 citation statements)
references
References 52 publications
29
185
9
5
Order By: Relevance
“…By further exploring our prior finding that RUNX is a prerequisite for the initiation of leukemia development (10,11), we now reveal that RUNX plays a pivotal role in the maintenance of leukemia cells as well as tumor cells derived from different origins. According to a previous report, the frequency of RUNX1 point mutations in the Runt domain among de novo adult AML cases is around 10% (41). Some of these mutant RUNX1 (such as D171N and S291fsX300 mutations) and RUNX1 fusion genes (such as RUNX1-ETO and RUNX1-ETO9a) are proven oncogenes in mice with a p53-proficient environment (42).…”
Section: Discussionmentioning
confidence: 99%
“…By further exploring our prior finding that RUNX is a prerequisite for the initiation of leukemia development (10,11), we now reveal that RUNX plays a pivotal role in the maintenance of leukemia cells as well as tumor cells derived from different origins. According to a previous report, the frequency of RUNX1 point mutations in the Runt domain among de novo adult AML cases is around 10% (41). Some of these mutant RUNX1 (such as D171N and S291fsX300 mutations) and RUNX1 fusion genes (such as RUNX1-ETO and RUNX1-ETO9a) are proven oncogenes in mice with a p53-proficient environment (42).…”
Section: Discussionmentioning
confidence: 99%
“…In FPD/AML, > 40 different RUNX1 mutations are described and show varied distribution at many different sites [13], but they are expected to occur with a VAF near to 50 or 100%. Additional prototypic mutations of AML such as DNMT3A , NRAS , and SRSF2 in 2 patients, and PTPN11 and TET2 in 1 patient each, respectively, were detected (Table 1); these mutations as well as the tetrasomy 13 of cases 1 and 4 being prototypic for RUNX1 -mutated AML subcohorts of larger studies [14]. All cases were devoid of t(8: 21).…”
Section: Novel Insightsmentioning
confidence: 99%
“…15,16 Although RUNX1 has been shown to exhibit both oncogenic and oncosuppressive properties context-dependently in various cancers, little has been known about the molecular mechanisms underlying this curious bidirectional function of RUNX1. 3,5,15,17,18 In addition, although mutations in RUNX1 have been reported to demarcate poorer-prognostic cohorts in AML patients, [19][20][21] the level of RUNX1 expression itself has not been directly linked to the outcomes of AML patients. Recently, we have reported that RUNX cluster regulation is a promising therapeutic strategy against various types of cancers, including AML.…”
Section: Discussionmentioning
confidence: 99%